2020
DOI: 10.1038/s41467-020-14357-2
|View full text |Cite
|
Sign up to set email alerts
|

Topological ultranodal pair states in iron-based superconductors

Abstract: Bogoliubov Fermi surfaces are contours of zero-energy excitations that are protected in the superconducting state. Here we show that multiband superconductors with dominant spin singlet, intraband pairing of spin-1/2 electrons can undergo a transition to a state with Bogoliubov Fermi surfaces if spin-orbit coupling, interband pairing and time reversal symmetry breaking are also present. These latter effects may be small, but drive the transition to the topological state for appropriate nodal structure of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a Bogoliubov Fermi surface in this system would naturally explain why a relatively clean superconductor can support a finite density of quasiparticles, as reflected in the residual Sommerfeld coefficient and the differential conductance seen in STM [246,250]. Clearly, independent verification of the assumed time reversal symmetry breaking is needed before such an explanation can be accepted above more conventional ones, but the idea is intriguing.…”
Section: Bogoliubov Fermi Surface Scenariomentioning
confidence: 92%
“…One intriguing solution to this puzzle was put forward in reference [246], where it was suggested that the system might naturally make a transition into a topological state that manifested a so-called Bogoliubov Fermi surface, a locus of points in k-space that supported zero energy excitations at low temperature in the superconducting state. Note this manifold has the same dimension as that of the underlying normal state Fermi surface, i.e., a 2D patch in a system of three spatial dimensions, etc., as distinct from an unconventional superconductor with line or point nodes.…”
Section: Bogoliubov Fermi Surface Scenariomentioning
confidence: 99%
“…Such a Fermi surface is called the Bogoliubov Fermi surface (BFS). In superfluid 3 He and in cuprate superconductors [7][8][9][10], the BFS appears in the presence of superflow, while in systems with multiband energy spectrum or with broken time-reversal symmetry the BFS may exist even in the absence of superflow [11][12][13][14][15][16][17][18]. Note that in a nodal topological superfluid or in a cuprate superconductor the superflow explicitly breaks time-reversal and inversion symmetries, and thus origin of the BFS can be considered on a common ground in different systems.…”
Section: Introductionmentioning
confidence: 99%